Fluorescent and magnetic properties of two Cu(II) and Cd(II) coordination polymers based on semirigid tripodal carboxylate ligand. (10th January 2017) - Xue, Zhi-Jia; Wang, Xiao-Qing; Zhang, Xiao; Wang, Xiao-Xiao; Hu, Tuo-Ping
Graphical abstract: The coordination preferences of different metal ions in synthetic procedures based coordination polymers. Abstract: Two new coordination polymers, namely, {[Cu3 (BCPB)(HBCPB)(H2 BCPB)(H2 O)]·(CH3 OH)(H2 O)} n (1 ), and {[Cd(HBCPB)(1, 4-bib)1.5 ]·4H2 O} n (2 ) (H3 BCPB = 3, 5-bis(2-carboxy-phenoxy)-benzoic acid, 1, 4-bib = 1, 4-bis(1H-imidazol-4-yl)benzene), have been synthesized under hydrothermal conditions and characterized by single-crystal X-ray diffraction analysis, elemental analysis (EA), IR spectra (IR), powder X-ray diffraction (PXRD), and thermogravimetric (TG) analysis. The X-ray diffraction analysis reveals that complex1 is an interesting (3, 3, 5, 6)-connected 2D network of point symbol (3·4 2 )2 (3·4 3 ·5 2 ·6 3. 7)2 (3 2 ·4 2 ·5 2 ·6 2 ·7 2 ·8 2 ·9 3 )(4 2 ·6)2, and the complex2 is a 4-connected 3Ddia framework of point symbol (6 6 ). Furthermore, the magnetic property of1, and luminescence sensing of complexes1 and2 for small organic molecules were also investigated.